The Effect of Training and Development, ICT Skills, and Additional Employee Allowances on Teacher Performance - Ria Irawati; Ahmad Syarief Iskandar; St Marwiyah; Jalil Jalil (Jurnal Studi Guru dan Pembelajaran, 2022)
This study highlights the effect of (1) training and development, (2) Information and Communication Technology (ICT) skills, and (3) additional employee allowances (Tambahan Perbaikan Penghasilan or TPP) on teacher performance at UPT SMA Negeri I Palopo. This is a quantitative study in an ex post facto correlational design. The population includes the 60 entire teachers at UPT SMA Negeri 1 in Palopo City, from which a sample size is calculated using Slovin’s formula at a 5% confidence level. Instrument of data collection fits in a 5-scale Thurstone questionnaire that measures four variables, i.e., training and development(X1), ICT skills (X2), additional employee allowances(X3), and teacher performance (Y). SPSS 23 is used to run multiple regression for data analysis. Findings indicate that the partialeffect of X variables on teacher performance at UPT SMA Negeri 1 Palopo is 25,7% (training and development-X1), 43,1% (ICT skills-X2), and38,2% (additional employee allowances-X3). In terms of simultaneity, the influence of X variables on teacher performance is 45%. These findings suggest that the constructs of training and development, ICT skills, and additional employee allowance, both partially and simultaneously, are helpful for aiding in the improvement model of teacher performance. UPT SMA Negeri 1 Palopo can use these findings to define performance quality plan for its entire teacher workforce.